Amount of the rice stubble on the weeds and the beans (Phaseolus vulgaris L.). - Herrera Murillo, Franklin (2003)
The assay was conductedbetween June 2000 and January 2001 at the Fabio BaudritExperiment Station of the University of Costa Rica, locatedin the San Jose district, in Alajuela, Costa Rica. The objectiveof the trial was to assess the influence of 0; 1.85; 3.70; 5.60;7.40 and 11 metric tons/ha (mt/ha) of dry matter of ricestubble (Var. CR-5272) as dead mulch on the ground surface,on the weeds and on the yield of the Huasteco bean variety,planted with least tilling. It was found that the rice stubble, inamounts over 3.7 mt/ha on the ground, drastically diminishedthe number of weeds, due mainly to the reduction of thetemperature fluctuations and the percentage ofphotosynthetic active and total light that reached the soilsurface. Besides, it improved the moisture holding capacityof the soil. The favorable effects of these factors werereflected in a greater production of bean grains.